ملخص: وعى أعضاء هیئة التدریس بجامعة جنوب الوادى بالانتحال العلمى - د. دعاء البرى (المجلة الدولية لعلوم المكتبات والمعلومات)
Plagiarism is the use of another scholar’s ideas or words without properaccreditation. It occurs mostly due to the lack of awareness and poor researchskills. The current study was undertaken to investigate the awareness aboutplagiarism among the academic staff at the South Valley University (SVU), itscauses and the policy that should be taken by the SVU against plagiarismpractices. The stratified random sampling method was used to investigate theawareness of academic staff at SVU about different types of plagiarism.Academic staff (157) from different faculties at SVU were surveyed through anonline questionnaire. The Vice President of SVU for the academic affair andpostgraduate research was interviewed to ensure the presence of policy to dealwith plagiarism cases. The findings revealed that only about 60% of the academicstaff at the SVU were aware about plagiarism with varying levels of awareness ofdifferent types of plagiarism among. Most of the staff was aware of completeplagiarism (99.4%), followed by misleading attribution (82.2%), verbatim (79%),repetitive research (67.5%), paraphrasing (66.9%), duplication (63.1%),secondary source (49%), invalid source (47.8%), unethical collaboration (33.1%)and replication (17.8%). The study revealed some causes of plagiarism such asare poor awareness, lack of writing skills and absence of definite policy ofpunishment on plagiarized researchers. The study reported that there is noauthorized policy to deal with plagiarizers at SVU. The author recommendstraining of the staff of SVU to promote awareness about the different types ofplagiarism and its implications, improving their writing skills and applying adefinite policy against proven cases of plagiarism. Further focused studies arerequired to investigate the awareness of academic staff about plagiarism in otherEgyptian Universities and to test strategies to prevent it.